Prevalence of Self-Medication Practice and Associated Factors among Pregnant Women Who Attended Antenatal Care at Public Hospitals of North Shewa Zone, Amhara Region, Ethiopia - Abrham Demis; Birhanetensay Masresha Altaye; Mulugeta Emiru; Mitiku Tefera (Advances in Pharmacological and Pharmaceutical Sciences)
Background. Self-medication practice is the use of medicine without consulting health professionals to treat self-recognized illness by the general population including pregnant women. Inappropriate self-medication practice during pregnancy may pose harmful consequences for the fetus as well as the mother. There is not given much attention on the practice of self-medication among pregnant women in our setting. Therefore, this study aimed to assess the prevalence of self-medication practice and associated factors among pregnant women who attended antenatal care at North Shewa Zone public hospitals. Methods. An institution-based cross-sectional study was conducted from June 01, 2022 to July 30, 2022, among 650 pregnant women who attended antenatal care at North Shewa Zone public hospitals. A multistage sampling technique was employed. The questionnaires were pretested. A structured interviewer-administered questionnaire and reviewed medical records were used for data collection. Epi-data version 4.6.2 and SPSS version 20 were utilized for data entry and analysis, respectively. Bivariate and multivariable logistic regression was done to identify associated factors, and P values less than 0.05 were considered statistically significant. Results. The prevalence of self-medication practice among pregnant women was 65.38%. Housewives (AOR = 0.097 95% CI 0.030, 0.310), farmers (AOR = 0.117, 95% CI 0.028, 0.493), people with health insurance (AOR = 0.507, 95% CI 0.300, 0.858), and people in preconception care (AOR = 0.038, 95% CI 0.011–0.135) were less likely to practice self-medication, while people with primary education (AOR = 3.00, 95% CI 1.217, 7.435), income less than 3,000 birr (AOR = 5.46, 95% CI 1.41, 21.1), participants in the first (AOR = 4.183, 95% CI 2.12, 8.24) and second trimesters (AOR = 2.05, 95% CI 1.18, 3.56), pregnant women who lived in rural areas (AOR = 1.579, 95% CI 1.103–2.260), and people who previously practiced self-medication (AOR = 8.2, 95% CI 5.04, 13.3) were more likely to practice self-medication. Conclusion. From the present finding, it can be concluded that self-medication among pregnant women is high. Previous self-medication practice, gestation period, educational status, monthly income, no preconception care, no health insurance, being a housewife, farmer, and place of residence were significantly associated with self-medication practice. Therefore, preventive measures such as proper counseling during dispensing, awareness creation programs on preconception care, and enrolling in health insurance programs to minimize the practice of self-medication are necessary.